2013
DOI: 10.1111/jpc.12160
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and asthma at school entry: Co‐morbidities and temporal trends

Abstract: The pattern of association with co-morbidities was different for asthma and obesity. The temporal decline/plateau effect in 'current asthma' could not be explained by concurrent body mass index changes. The decline in obesity was largely driven by the 2005 findings. Longer term trends need to be evaluated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The mean asthma prevalence across the seven years included in the present analysis was 11%, with a higher prevalence evident in boys and overweight/obese participants relative to girls and normal weight participants, respectively. This association between obesity and asthma is in accord with previous studies (Black et al 2012;Figueroa-Muñoz et al 2001;Gennuso et al 1998;Luder et al 1998), as is the gender difference (Anthracopoulos et al 2011;Hansen et al 2013;James et al 2013).…”
Section: Discussionsupporting
confidence: 92%
“…The mean asthma prevalence across the seven years included in the present analysis was 11%, with a higher prevalence evident in boys and overweight/obese participants relative to girls and normal weight participants, respectively. This association between obesity and asthma is in accord with previous studies (Black et al 2012;Figueroa-Muñoz et al 2001;Gennuso et al 1998;Luder et al 1998), as is the gender difference (Anthracopoulos et al 2011;Hansen et al 2013;James et al 2013).…”
Section: Discussionsupporting
confidence: 92%
“…A total of 1473 studies were identified whereof 355 were duplicates and 1025 were excluded on titles and abstract, leaving 93 papers for full text evaluation. Of these, 24 original studies, two meta‐analyses and one additional study from the manual search of references were included 8,14‐39 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…After review of the titles and abstracts, 536 articles did not meet our inclusion criteria, and 12 were excluded 31-42 for a lack of data for the frequency of AD/eczema or BMI classification. In total, 30 studies 26,33, were included in the review, of which 20 had valid data that could be pooled to assess for the effects of overweight, 26,43,47,50,[53][54][55][56][57][59][60][61][62][63][64][65][66][67][68][69] 23 for obesity, 26,33,43,45,47,50,[52][53][54][55][56][57][59][60][61][62][63][64][65][66][67][68][69] and 26 for overweight/obesity. 26,43,44,[46]…”
Section: Literature Searchmentioning
confidence: 99%